Chemical Functionalization and Characterization of Cellulose Extracted from Wheat Straw Using Acid Hydrolysis Methodologies - Chemar J. Huntley; Kristy D. Crews; Michael L. Curry (International Journal of Polymer Science)
The nonuniform distribution of cellulose into many composite materials is attributed to the hydrogen bonding observed by the three hydroxyl groups located on each glucose monomer. As an alternative, chemical functionalization is performed to disrupt the strong hydrogen bonding behavior without significant altering of the chemical structure or lowering of the thermal stability. In this report, we use wheat straw as the biomass source for the extraction of cellulose and, subsequently, chemical modification via the Albright-Goldman and Jones oxidation reactions. X-ray diffraction analyses reveal that upon oxidation a slight change in the cellulose polymorphic structure (CI to CII) can be observed when compared to its unmodified counterpart. Scanning electron microscopy analyses show that the oxidized cellulose structure exhibits fiber-like crystals with lengths and diameters on the micrometer scale. Thermal analyses (differential scanning calorimetry and thermogravimetric analysis) show an increase in the thermal stability for the modified cellulose at extremely high temperatures (>300°C).